Meningkatkan Hasil Belajar Bahasa Indonesia melalui Model Kooperatif STAD untuk Siswa Kelas XI MIA4 SMA Negeri 2 Bangkinang Kota Tahun Pelajaran 2016/2017 - Yurnawilis, Yurnawilis (GERAM, 2018)
Classroom action research has been done in SMA Negeri 2 Bangkinang Kota on Indonesian Language subjects with research object of class XI MIA 4 in odd semester 2016/2017. This study was conducted as an effort to improve the learning ability of Indonesian for students of class XI MIA 4. STAD type was chosen to be applied after through observation and reflection conducted by the researcher. Researchers plan actions based on observations and reflections that have been done through the preparation of STAD type learning based learning tools consisting of Cycle I / test questions, and Cycle II test/test, observation sheet and lesson plan and other supporting learning tools. The implementation of STAD type cooperative learning in the learning process through the preparation stage, class presentation, group activities, carry out evaluation, group awards and recalculate basic scores and group changes. This study can be completed in 2 cycles 6 meetings, at meeting 3 and 6 meeting conducted test / repeat and complete recapitulation of learning showed that there has been an increase of positive student learning activity in class and increasing of test mean (repetition) and also increase of classical completeness from cycle I with cycle II. Student activity during the learning process is observed by the observer as data for evaluation and reflection. Average recapitulation of test (repetition) and learning completeness obtained from the value of the test in cycle 1 and the value of tests in cycle 2. Based on the results of research can be concluded that the application of learning with STAD type in class XI MIA 4 SMA Negeri 2 Bangkinang City able to improve learning outcomes subjects Indonesian language is indicated by the average test (repetition) and classical completeness in every cycle.